Teachers' attitudes towards the use of educational games in developing creative thinking among children in Hafr Al-Batin - Al-Mutairi, Nouf Nahar (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the tendencies teachers towards the use of educational games in developing creative thinking among children in Hafr Al-Batin. The data from the study sample members, which consisted of (162) female teachers, who were chosen by the simple random method. The researcher developed a tool that consisted of (32) items. The results of the study showed that the kindergarten teachers’ attitudes towards using educational games in developing creative thinking were high. The results also showed that there were no statistically significant differences in the attitudes of female teachers towards the use of educational games in developing creative thinking due to the variables of academic qualification, work sector, years of experience.In light of the results, the study concluded a number of recommendations, including: that educational games in the school curricula become an essential means of education for teachers to use to develop creative thinking among children, and the formation of specialized educational and technical committees to set standards and foundations for choosing individual and group educational games that are appropriate with children so as to stimulate growth The child's mental and creative thinking and works to achieve social growth and increase linguistic and emotional development
Keywords: Attitudes; Educational games; creative thinking